Navigating Recovery, Stigma, and Mood Fluctuations: A Phenomenological Study of Adolescents with Bipolar Disorder in Yogyakarta - Finda Pensiuna Wati; Fx. Wahyu Widiantoro (Universitas Ahmad Dahlan, 2026)
Bipolar disorder in adolescence can disrupt emotional regulation, identity development, and social functioning during a critical transition to adulthood. This phenomenological study explored adolescents’ lived experiences of bipolar disorder within the mental health recovery process in Yogyakarta. Three adolescents diagnosed with bipolar disorder participated in in-depth interviews complemented by observational notes. Data were analyzed using an interactive qualitative analysis approach. Participants understood recovery as a dynamic, ongoing effort to manage emotions, rebuild routines, and maintain hope rather than complete symptom remission. Mood fluctuations were experienced as rapid, intense, and unpredictable shifts that drained energy, interfered with school and daily activities, and strained relationships with peers and family. Stigma emerged as a central psychosocial barrier: public stigma and environmental misunderstanding, together with self-stigma, promoted concealment, social withdrawal, and ambivalence toward seeking help. Despite these pressures, participants described coping and support as protective resources, including self-monitoring and reflection, journaling, routine management, and support from family and mental health professionals. These findings imply that adolescent services should be recovery-oriented, integrating mood monitoring and sleep/routine stabilization with stigma reduction, family psychoeducation, school-based mental health literacy, and accessible psychosocial support. Programs that strengthen coping skills and supportive relationships are recommended to improve sustained adjustment and recovery trajectories.